Analisis Semiotika Inklusifitas Tunanetra dalam Tayangan Youtube ‘Bang Jack Itu Buta, Bukan Bego’ - Yusandi, Rakha Alifiano; Mudzakkir, Moh. (Paradigma, 2026)
This study aims to analyze the representation of visually impaired individuals and the construction of inclusiveness in the digital media space through the YouTube video titled "Bang Jack Itu Buta, Bukan Bego." Using a qualitative method with Roland Barthes' semiotic approach, this research examines key segments, dialogues, gestures, and audio-visual elements within the video under a constructivist paradigm. Data collection was carried out through documentation and non participant observation by transcribing, categorizing, and analyzing the video content. The findings reveal that the video successfully deconstructs dominant social myths that represent visually impaired people as passive, helpless, emotionally fragile, and economically disadvantaged. At the denotative and connotative levels, Bang Jack represented as a stand-up comedian and activist redefines blindness as an objective "condition" and "identity" rather than a pitied "disability." Furthermore, the study indicates that true inclusiveness is constructed through a triad of dimensions: natural social interaction spaces, consistent public infrastructure, and collective behavioral shifts (attitude) in society. In conclusion, the media serves as an effective sociological instrument to challenge physical accessibility barriers and dismantle systemic stereotypes, fostering a more empowered and autonomous identity for people with visual impairments. Keywords: Inclusivity, Roland Barthes' Semiotics, Visually Impaired, Identity, Stereotypes, Youtube